'Guard the Good Deposit':‡ Technology, Provenance and Dating of Bipyramidal Iron Semi‐Products of the Durrenentzen Deposit (Haut‐Rhin, France). (27th April 2017) - Bauvais, S.; Berranger, M.; Boukezzoula, M.; Leroy, S.; Disser, A.; Vega, E.; Aubert, M.; Dillmann, P.; Fluzin, P.
Abstract : In the early days of iron metallurgy in Western Europe, the most widespread type of 'trade iron' (semi‐product) was bipyramidal in shape. Although they are frequently found, little is known about how they were manufactured and circulated, or even about their age. An interdisciplinary approach was applied to the Durrenentzen deposit (Haut‐Rhin, France), the third‐largest in Europe in terms of artefact quantities, in an attempt to reconstruct the technological, social and economic context that caused them to be abandoned. A morphometric study of the 51 iron bars revealed a high degree of homogeneity, despite variations in detail. Four objects were selected for archaeometric studies. Metallographic analyses show internal differences (quality of the material, nature of the alloys and manufacturing techniques). Chemical analyses also showed different provenances. Finally, radiocarbon analyses of the carbon in steel (iron/carbon alloy) linked this deposit to the early Iron Age. This study provided the first benchmark for more general research, significantly changing perceptions of the economics of iron at the beginning of the Iron Age.